Assessment of nurse’s perceived just culture: a cross-sectional study - Kenneth Jun Logroño (17541258) (2023)
Background The non-punitive approach to error investigation in most safety culture surveys have been relatively low. Most of the current patient safety culture measurement tools also lack the ability to directly gauge concepts important to a just culture (i.e. perceptions of fairness and trust). The purpose of this study is to assess nurses’ perceptions of the six just culture dimensions using the validated Just Culture Assessment Tool (JCAT). Methods This descriptive, cross-sectional study was conducted between November and December 2020. Data from 212 staff nurses in a large referral hospital in Qatar were collected. A validated, self-reported survey called the JCAT was used to assess the perception of the just culture dimensions including feedback and communication, openness of communication, balance, quality of event reporting process, continuous improvement, and trust. Results The study revealed that the overall positive perception score of just culture was (75.44%). The strength areas of the just culture were “continuous improvement” dimension (88.44%), “quality of events reporting process” (86.04%), followed by “feedback and communication” (80.19%), and “openness of communication” (77.55%) The dimensions such as “trust” (68.30%) and “balance” (52.55%) had a lower positive perception rates. Conclusion A strong and effective just culture is a cornerstone of any organization, particularly when it comes to ensuring safety. It places paramount importance on encouraging voluntary error reporting and establishing a robust feedback system to address safety-related events promptly. It also recognizes that errors present valuable opportunities for continuous improvement. Just culture is more than just a no-blame practice. By prioritizing accountability and responsibility among front-line workers, a just culture fosters a sense of ownership and a commitment to improve safety, rather than assigning blame. Other Information Published in: BMC Nursing License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12912-023-01478-4